Systematic location of the public logistic centres in Czech Republic - Kampf, Rudolf; Průša, Petr; Savage, Christopher (Transport, 2011)
This article is focusing on exploring parameters, which are needed to determine the most suitable location for public logistic centres in the Czech Republic. There is a wide range of factors, which will have an impact on the chosen location. It is not easy to define all the factors and include them into one model, especially because some of them are difficult to quantify. The aim of the research is to design a suitable tool to support the decision making process for the location of the public logistic centres. As public logistic centres will be partly financed by the Czech government, it is necessary to find a sensible tool as decision support. First Published Online: 09 Jan 2012